2021
DOI: 10.1177/23259671211001069
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ulnar Collateral Ligament Repair With Internal Brace Augmentation on Articular Contact Mechanics: A Cadaveric Study

Abstract: Background: There has been renewed interest in ulnar collateral ligament (UCL) repair in throwing athletes because of a greater understanding of UCL injuries, improvement in ligament repair technology, and potentially expedited rehabilitation time and return to play relative to UCL reconstruction. Purpose: To evaluate elbow articular contact and overall joint torque after UCL reconstruction and repair augmented with a collagen-coated fiber tape, InternalBrace. Study Design: Controlled laboratory study. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…However, these studies also showed greater resistance to gap formation during subfailure fatigue testing in the repair group. 39,42 Roth et al 23 in 2021 examined the effect on joint contact mechanics in an augmented repair and a modified Jobe reconstruction technique. They noted no difference in contact pressures between the groups and no statistically significant difference from the intact state.…”
Section: Ucl Repair Techniques and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these studies also showed greater resistance to gap formation during subfailure fatigue testing in the repair group. 39,42 Roth et al 23 in 2021 examined the effect on joint contact mechanics in an augmented repair and a modified Jobe reconstruction technique. They noted no difference in contact pressures between the groups and no statistically significant difference from the intact state.…”
Section: Ucl Repair Techniques and Resultsmentioning
confidence: 99%
“…However, these studies also showed greater resistance to gap formation during subfailure fatigue testing in the repair group 39,42. Roth et al 23. in 2021 examined the effect on joint contact mechanics in an augmented repair and a modified Jobe reconstruction technique.…”
Section: Ucl Repair Techniques and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Additionally, native UCL repair with suture augmentation with an InternalBrace (Arthrex) has been shown to have equivalent time-zero biomechanical properties to the native ligament and reconstructed ligament using the docking and modified Jobe techniques. 2 , 9 , 13 , 21 Our technique also utilizes a high-strength suture acting as a biologic internal brace to allow partial shielding of valgus stress during the early repair phases of ligament healing. It is not beyond reason to assume that the biomechanical properties of native UCL repair extend to repairs of the UCL graft.…”
Section: Discussionmentioning
confidence: 99%
“…The prepared specimens were then loaded into a custom testing fixture that was previously described as appropriate for UCL torque and contact pressure testing. 16 This was mounted into a servohydraulic mechanical test frame (MTS Systems) with torsional capabilities. The elbow joint was distracted minimally in approximately 30° to 45° of flexion to allow for insertion of a single branch of the pressure sensor into the ulnohumeral joint space ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%